1988
DOI: 10.1007/bf02303122
|View full text |Cite
|
Sign up to set email alerts
|

Interannual correlations between sea level difference at the south coast of Japan and wind stress over the north pacific

Abstract: Relationships of the sea level differences between Naze and Nishinoomote and between Kushimoto and Uragami with wind stress over the North Pacific are examined for interannual variability. These sea level differences are considered to be indications of Kuroshio transport in Tokara Strait and Kuroshio path south of Enshu-nada, respectively.In the sea level difference between Kushimoto and Uragami, dominant variations are found to have periods of about seven years and 3-4 years. The variation of about 7-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The spatial coherence covers the subtropical and subarctic areas as well as the tropical area. This is consistent with the results of Kutsuwada (1988bKutsuwada ( , 1990, who showed that there are signals with a period of 3-4 years in the western portions of the subtropical and subarctic gyres. It is considered that EN-period variations are related to global-scale features of the ENSO variability.…”
Section: Discussionsupporting
confidence: 92%
“…The spatial coherence covers the subtropical and subarctic areas as well as the tropical area. This is consistent with the results of Kutsuwada (1988bKutsuwada ( , 1990, who showed that there are signals with a period of 3-4 years in the western portions of the subtropical and subarctic gyres. It is considered that EN-period variations are related to global-scale features of the ENSO variability.…”
Section: Discussionsupporting
confidence: 92%
“…Wind stress curl forcing with periods above 300 days generates large‐scale baroclinic Rossby waves [ Willebrand et al , 1980; Pierini , 1998]. Both of these relationships between the wind stress curl and WBC flow have been confirmed by observations [ Moore and Wilkin , 1998; Sturges and Hong , 2001; Lee et al , 1996; Kutsuwada , 1988].…”
Section: Introductionmentioning
confidence: 81%
“…Care must be taken in the southern site, where the correlation is borderline significant at best and where AWS might be the forcing behind it. References to an interannual signal relating the interior Sverdrup transport to WBC flows, as observed in the north location, also exist but are less abundant [ Kutsuwada , 1988]. An immediate explanation is the paucity of long‐term records.…”
Section: Discussionmentioning
confidence: 99%
“…It can be easily imagined an importance of a baroclinic mechanism for interannual variation of the Kuroshio because of the long time scale of a baroclinic response. However, Kutsuwada (1988) pointed out that interannual variation in sea level difference across the Tokara Strait is coherent with that of the zonally-integrated Sverdrup transport in the latitudinal zone along 30°N. His result suggests that the interannual variation of the Kuroshio transport at the Tokara Strait can be explained by the barotropic response to the wind stress.…”
Section: Summary and Discussionmentioning
confidence: 96%